Why people get lost the psychology and neuroscience of spatial cognition - Dudchenko, Paul A. (Oxford : Oxford University Press, 2010)
At some point in our lives, most of us have been lost. How does this happen? What are the limits of our ability to find our way? Do we have an innate sense of direction? 'How People Get Lost' is an exploration of the psychology and neuroscience of how we find our way.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Orientation (Psychology); Space perception; Spatial ability; Navigation